Penerapan Lean Manufacturing Dengan Metode Value Stream Mapping Untuk Mengurangi Waste Pada Proses Pengecekan Material Bahan Baku Ke Lini Produksi - Fatma, Nur Fadilah; Ponda, Henri; Sutisna, Endang (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2022)
PT. Brigth Mobile Telemunnication is a manufacturing company that produces mobile phones, one of which is OPPO and REALME brand mobile phones. In fulfilling its production needs, PT Brigth Mobile Telecommunication works with suppliers in Indonesia. The delivery process at pt Brigth mobile telecommunications involves two divisions, namely the IQC division and the warehouse division. before sending the material must be checked first at the IQC division to prevent quality problems in the production line but delays in the delivery of raw material materials to the production line often occur due to the ineffectiveness of the checking process due to activities that do not provide added value which is a source of waste. Then the Value Stream Mapping Tools are used to identify and eliminate the waste. The purpose of this study was to determine the initial conditions of the company, as well as the final conditions after repairs using kaizen. From the research conducted, it was found that several wastes in the checking process include Transportation, Unappropriate processing (inappropriate process), Unnecessary motion (unnecessary movement)-waiting (waiting). And the result after the repair is done is the reduced time to complete the material checking process by combining several SOP and replacing the Acceptable Quality Level AQL 1 standard with the AQL S-3 standard to make it more effective because it is rare to find NG.Keywords: incoming quality control, checking process, Value Stream Mapping Tools, Waste, AQL (Acceptable Quality Level)